2013
DOI: 10.3144/expresspolymlett.2013.59
|View full text |Cite
|
Sign up to set email alerts
|

Multiwalled carbon nanotubes incorporated into a miscible blend of poly(phenylenether)/polystyrene – Processing and characterization

Abstract: Abstract. 4 wt% multiwalled carbon nanotubes (MWCNTs) were incorporated into a miscible blend of polyphenylenether/ polystyrene (PPE/PS) on a twin-screw extruder at a screw speed of 600 rpm. The masterbatch obtained was diluted at 400 and 600 rpm to obtain lower MWCNT loadings in PPE/PS. Electron microscopy & optical microscopy images show very good MWCNT dispersion even at high filler loadings of 4!wt%, but slightly larger agglomerate size fractions are observable at higher screw speeds. While MWCNT addition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 48 publications
(61 reference statements)
0
17
0
Order By: Relevance
“…Side feeding of the filler Nanocyl TM NC7000 which has a lower agglomerate strength is recommended owing to its loosely packed agglomerate structure with better dispersion envisioned by a dominant melt infiltration [84]. We have carried out comprehensive investigations on the influence of the twinscrew process parameters on MWCNT dispersion in PP, PS, PPE/PS and PC and have understood that the ideal processing parameters is strongly dependant on the nature of the matrix and its compatibility with the CNTs [65][66][67]83]. …”
Section: Influence Of Process Parametersmentioning
confidence: 99%
“…Side feeding of the filler Nanocyl TM NC7000 which has a lower agglomerate strength is recommended owing to its loosely packed agglomerate structure with better dispersion envisioned by a dominant melt infiltration [84]. We have carried out comprehensive investigations on the influence of the twinscrew process parameters on MWCNT dispersion in PP, PS, PPE/PS and PC and have understood that the ideal processing parameters is strongly dependant on the nature of the matrix and its compatibility with the CNTs [65][66][67]83]. …”
Section: Influence Of Process Parametersmentioning
confidence: 99%
“…Especially mould temperature and packing pressure are identified by Piscotti et al to have a high impact on color and gloss. Inhomogeneity in color across the material surface is often caused by insufficient dispersion of fillers or colorants, or by injection moulding parameters too [8,7].…”
Section: Related Workmentioning
confidence: 99%
“…This is why a considerable number of studies have been directed toward understanding parameters controlling the nanoparticle localization in polymer blends. It has been shown that the nanoparticle localization can be determined by thermodynamic parameters and more specifically by interfacial interaction between the nanoparticles and blend components or kinetic parameters, including the feeding sequence, viscosity of the blend components and mixing conditions [22][23][24]. It has been shown that the particle-particle and particle-polymer interactions have a major impact on the rheological as well as mechanical enhancement of fumed silica-filled nanocomposites due to the large surface area of particles.…”
Section: Introductionmentioning
confidence: 99%